﻿Pengajian Umum: pengalaman Universiti Putra Malaysia - Zaid Ahmad,; Sri Rahayu Ismail,; Ahmad Tarmizi Talib, (Universiti Kebangsaan Malaysia, 2010)

(untitled)
The aim of the paper is to report on the current status, experiences and the challenges faced by Universiti Putra Malaysia (UPM) in incorporating philosophy and human civilization, politics and governance in the compulsory courses offered by the Faculty of Human Ecology. The compulsory courses encompass the following subjects – languages, Islamic and Asia Civilization, Ethnic Relations, Malaysian Nationhood, Agriculture and Society.